IMPROVING ENGLISH VOCABULARY MASTERY THROUGH THE USE OF LEARNING CIRCUIT MODEL - Eksanti .; Nani Hidayati (Jurnal Ilmiah Penelitian Mahasiswa, 2022)
The aim of this study was to find out whether or not the use Circuit Learning Model is effective to improve students' vocabulary mastery of the first graders at SMP N 1 Kaliori in the academic year 2022/2023. The type of this study was a quasi-experimental research and the method was a quantitative method. The population of this study was the seventh graders of SMP N 1 Kaliori and the sample consisted of 30 students of VII 2 as the experimental class and 30 students of VII 6 as the control class. The try-out test for VII 1 class was done to know the validity and reliability of the instrument. Pre-test and post-test were given to the experimental and control class. The result was analyzed by using SPSS 26 version. The result of the pre-test for the experimental and control classes were 54.13 and 76.13. While the result of the post-test of the experimental and control class were 84.53 and 81.53. The post-test result from both classes were analyzed by using t-test. The result of the analysis shows that sig (2-tailed) 0.163 is ≥ 0.05 which means there was no significant difference in the result score between the control group and the experimental group. It was concluded that H1 was rejected and H0 was accepted. Therefore, the use of the circuit learning model to improve English vocabulary mastery for the seventh-grade students at SMP N 1 Kaliori was not effective. Some unpredicted factors which were out of control and need to be further researched can be the cause of the ineffectiveness.